Generative Models in Natural Language Processing: A Comparative Study of ChatGPT and Gemini - Alsajri, Abdulazeez; Salman , Hasan Ahmed; Steiti , Amani (Babylonian Journal of Artificial Intelligence, 2024)
Generative models in natural language processing (NLP) have transformed machine interactions with human language. This research offers a comparative examination of ChatGPT and Gemini, two cutting-edge NLP models. This research elucidates the distinct strengths and shortcomings of each model by analyzing conversational fluency, diversity, and contextual accuracy. ChatGPT has exceptional originality in word production, but Gemini excels in contextual variety and sophisticated learning methodologies. The results highlight the revolutionary capability of generative models in fields such as education, customer service, and content production. Anticipated future improvements in this field are projected to enhance these capabilities, promoting wider societal and industrial advantages.